Xylazine detected in unregulated opioids and drug administration equipment in Toronto, Canada: clinical and social implications - Jeanette M. Bowles; Karen McDonald; Nazlee Maghsoudi; Hayley Thompson; Cristiana Stefan; Daniel R. Beriault; Sarah Delaney; Ernest Wong; Dan Werb (BMC, 2021)
Abstract Background The North American opioid overdose crisis is driven in large part by the presence of unknown psychoactive adulterants in the dynamic, unregulated drug supply. We herein report the first detection of the psychoactive veterinary compound xylazine in Toronto, the largest urban center in Canada, by the city's drug checking service. Methods Toronto's Drug Checking Service launched in October 2019. Between then and February 2021, 2263 samples were submitted for analysis. The service is offered voluntarily at harm reduction agencies that include supervised consumption services. Samples were analyzed using gas chromatography-mass spectrometry or liquid chromatography-high resolution mass spectrometry. Targeted and/or untargeted screens for psychoactive substances were undertaken. Results In September 2020, xylazine was first detected by Toronto's Drug Checking Service. Among samples analyzed from September 2020 to February 2021 expected to contain fentanyl in isolation (610) or in combination with methamphetamine (16), xylazine was detected in 46 samples (7.2% and 12.5% of samples, respectively). Samples were predominantly drawn from used drug equipment. Three of the samples containing xylazine (6.5%) were associated with an overdose. Conclusion We present the first detection of xylazine in Toronto, North America's fourth-largest metropolitan area. The increased risk of overdose associated with use of xylazine and its detection within our setting highlights the importance of drug checking services in supporting rapid responses to the emergence of potentially harmful adulterants. These data also highlight the clinical challenges presented by the dynamic nature of unregulated drug markets and the concomitant need to establish regulatory structures to reduce their contribution to overdose morbidity and mortality.